Frictionless flow in channels - Chan, Freddie Yang Wei. (2012)
This project explores seven surface groove designs with the aim of achieving friction reduction in fluid flows. An experiment was designed and fabricated to substantiate theoretical analysis as well as to observe fluid behaviour in channel flow. The pressure difference (ΔP) of water flow across each surface specimen was recorded. The results showed that the 0.8mm surface specimens increased drag and thus failed as drag reduction devices. All 0.4mm and 0.6mm surface specimens displayed drag reduction properties.